RELASI GERAKAN SOSIAL POLITIK PONDOK PESANTREN (STUDI KASUS PADA PONDOK PESANTREN ASSULAMY DESA LANGKO KECAMATAN LINGSAR KABUPATEN LOMBOK (BARAT) - Wahyu Trisno Aji (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research aims to see how the relationship between social and political movements of Islamic boarding school foundations. Assulamy Islamic boarding school, Langko village, Lingsar sub-district, West Lombok district, Assulamy Islamic boarding school as an Islamic educational institution, has unique characteristics as shared community property, not private ownership. The impact can be felt widely by the people of Langko Village because this Islamic boarding school specifically pays attention to and meets the educational needs of the environment. The socio-political relationship between the Assulamy Islamic Boarding School and the Langko Village community can be considered harmonious, reflected in the positive contribution and impact the Islamic boarding school has had on the local community. The interests and important role of the leadership of the Assulamy Islamic Boarding School, especially H. Jamhur, make this Islamic boarding school a source of pride for its community. Public trust in every decision and action of the leadership of the Assulamy Islamic Boarding School, which is reflected in H. Jamhur’s success when running for DPRD membership in NTB, shows that harmonious socio-political relations with the community have had a positive impact at the political level. Keywords : Assulamy Islamic boarding school, social and political movements, Langko village